2021
DOI: 10.3390/catal11080968
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Asymmetric Simmons-Smith Cyclopropanation and Diethylzinc Addition to Aldehydes Promoted by Enantiomeric Aziridine-Phosphines

Abstract: During an implementation of current research, a set of optically pure chiral aziridines and aziridine imines bearing a phosphine moiety was prepared with high values of chemical yield. The above chiral heteroorganic derivatives were tested for catalytic utility as chiral ligands in asymmetric Simmons-Smith cyclopropanation and asymmetric diethylzinc addition to various aldehydes. Most of the desired products were formed in high chemical yields, with satisfactory values of enantiomeric excess (sometimes more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Aziridines were also reported to be useful catalysts. 95 Rachwalski and co-workers described an asymmetric Morita–Baylis–Hillman reaction of methyl vinyl ketone and methyl acrylate ( 339 ) with various aromatic aldehydes ( 340 ) using chiral aziridine-phosphines ( 341 ) as chiral catalysts (Scheme 60). 96…”
Section: Aziridines As Reaction Intermediates and Catalystsmentioning
confidence: 99%
“…Aziridines were also reported to be useful catalysts. 95 Rachwalski and co-workers described an asymmetric Morita–Baylis–Hillman reaction of methyl vinyl ketone and methyl acrylate ( 339 ) with various aromatic aldehydes ( 340 ) using chiral aziridine-phosphines ( 341 ) as chiral catalysts (Scheme 60). 96…”
Section: Aziridines As Reaction Intermediates and Catalystsmentioning
confidence: 99%
“…Diethylzinc (Et 2 Zn) is a metal organic compound which is widely used for the purpose of organic synthesis. [27][28][29][30] Okura et al developed a coupling reaction for alkynylzinc reagents with aryl and alkenyl iodides and without the aid of transition metal catalysis by mixing and heating all the materials including terminal alkynes and Et 2 Zn (in a 2 : 1 ratio). [31] Huang et al reported the first example of Et 2 Zn mediated silylation of 1-aklynes and chlorosilanes and mechanistic studies that support Zn alkynilides as intermediates in the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral aziridines are useful intermediates in the synthesis of biologically significant compounds due to their ability to undergo nucleophilic ring opening reactions [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Considering our previous results on carbohydrate chemistry [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and based on our experience in synthesis and catalytic activity in the asymmetric synthesis of chiral aziridines [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ], we decided to couple aziridines to glycals with D-gluco and D-galacto configurations via C -glycosidic bonding, with the final formation of C -glycosyl-aminoethyl sulfide derivatives.…”
Section: Introductionmentioning
confidence: 99%